PERENCANAAN BENDUNG PROGO JUMO,SUNGAI PROGO KABUPATEN TEMANGGUNG - Bhre Brahmasta Indra; Lintang Jata Angghita; Sri Eko Wahyuni; Dwi Kurniani (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
Progo Jumo Weir is located on Progo River, Temanggung Regency. Progo Jumo Weir only serve the irrigation area in the left side of Progo River that formerly are rainfed rice field with 1.278 Ha wide. The maksimum intake discarge is 1,942 m3/sec. FJ Mock method is used to calculate the dependable discharge of Progo river at 20% dry. Designed flood discharge calculated from HSS Gama I method is 186,041 m3/sec for 100 years return period (Q100 = 186,041 m3/sec). Rounded weir head with 4,85 m in height and +713,07 m from mean sea level is used. The weir is 39 m in effective width and the length of upstream apron floor is 8 m. . This weir use USBR Type III stilling basin with 8 m in length. The flushing gate uses four gates each 1,5 m in width. The implementation of this project is 42 weeks and the budget plan is Rp. 13.210.231.000,00.